Preamble‐aided time delay estimation in frequency selective channels for wireless OFDM systems. Issue 8 (28th August 2014) - Yu, Qun; Lin, Haisheng; Feng, Suili; Li, RongLin
Abstract : In this Letter, an improved method for estimating the time delay in preamble‐aided orthogonal frequency division multiplexing systems is presented. It uses a conventional preamble structure and combines cross‐correlation techniques to achieve estimations of time delay and the number of multipaths without any additional overhead. Computer simulations results show that the proposed method is of near‐ideal property in frequency‐selected channels.